Designing soft materials with interfacial instabilities in liquid films. Issue 1 (December 2018) - Marthelot, J.; Strong, E.; Reis, P.; Brun, P.-T.
Abstract Natural soft materials harness hierarchy and structures at all scales to build function. Adapting this paradigm to our technological needs, from mechanical, phononic and photonic metamaterials to functional surfaces prompts the development of new fabrication pathways with improved scalability, design flexibility and robustness. Here we show that the inherent periodicity of the Rayleigh–Taylor instability in thin polymeric liquid films can be harnessed to spontaneously fabricate structured materials. The fluidic instability yields pendant drops lattices, which become solid upon curing of the polymer, thereby permanently sculpting the interface of the material. We solve the inverse design problem, taming the instability, so that the structures we form can be tailored, over a range of sizes spanning over two decades. This all-in-one methodology could potentially be extended down to the scales where continuum mechanics breaks down, while remaining scalable. Interfacial instabilities can be damaging as they may lead to fabrication defects. Here the authors harness a fluid instability to their advantage to produce thin polymeric films with drop-shaped structures which have tailored geometrical properties.